Substantial inter-individual and limited intra-individual genomic diversity among tumors from men with metastatic prostate cancer - Kumar, Akash (Nat Med, 2016)
Intra-individual tumor heterogeneity may reduce the efficacy of molecularly guided systemic therapy for cancers that have metastasized. To determine whether the genomic alterations in a single metastasis provide a reasonable assessment of the major oncogenic drivers of other dispersed metastases within an individual, we analyzed multiple tumors from men with disseminated prostate cancer by whole exome sequencing, array CGH and RNA transcript profiling and compared the genomic diversity within and between individuals. In contrast to substantial heterogeneity between men, there was limited diversity comparing metastases within an individual. Numbers of somatic mutations, the burden of genomic copy number alterations, and aberrations in known oncogenic drivers were highly concordant as were metrics of androgen receptor (AR) activity and cell cycle activity. AR activity inversely associated with cell proliferation, whereas the expression of Fanconi anemia (FA) complex genes correlated with elevated cell cycle progression, E2F1 expression and RB1 loss. Men with somatic aberrations in FA complex genes or ATM exhibited significantly longer treatment response durations to carboplatin compared to men without defects in genes encoding DNA repair proteins. Collectively, these data indicate that though exceptions exist, evaluating a single metastasis provides a reasonable assessment of the major oncogenic driver alterations present in disseminated tumors within an individual, and may be useful for selecting treatments based on predicted molecular vulnerabilities.